2003
DOI: 10.1136/jcp.56.11.840
|View full text |Cite
|
Sign up to set email alerts
|

Parasite detection in patients with post kala-azar dermal leishmaniasis in India: a comparison between molecular and immunological methods

Abstract: Aims: To evaluate the sensitivity and specificity of serological, immunohistochemical, and molecular methods in the diagnosis of post kala-azar dermal leishmaniasis (PKDL). Methods: Twenty five patients with confirmed PKDL and 25 controls were included in the study. G2D10, a monoclonal antibody against Leishmania, was used for the immunohistochemical (IHC) staining of lesion sections to visualise anti-Leishmania donovani antibodies. The diagnostic usefulness of IHC was compared with enzyme linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
4
38
0
1
Order By: Relevance
“…Such variable detection rates were considered to be caused because the diagnostic results of skin smear microscopy vary from person to person, and because it is prone to be influenced by the distribution of parasites throughout the skin tissue from which the skin biopsy was taken. Our results are in accordance with other authors who reported higher positive rates for PCR than for other detection methods (12,15). Although high detection rates of Leishmania DNA by PCR in suspected PKDL patients have been reported, lower rates were described when slit skin specimens were used for PCR; 42.9z in Bangladesh (12/28) (15), 82.7z in Sudan (19/23) (10).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Such variable detection rates were considered to be caused because the diagnostic results of skin smear microscopy vary from person to person, and because it is prone to be influenced by the distribution of parasites throughout the skin tissue from which the skin biopsy was taken. Our results are in accordance with other authors who reported higher positive rates for PCR than for other detection methods (12,15). Although high detection rates of Leishmania DNA by PCR in suspected PKDL patients have been reported, lower rates were described when slit skin specimens were used for PCR; 42.9z in Bangladesh (12/28) (15), 82.7z in Sudan (19/23) (10).…”
supporting
confidence: 78%
“…Although high detection rates of Leishmania DNA by PCR in suspected PKDL patients have been reported, lower rates were described when slit skin specimens were used for PCR; 42.9z in Bangladesh (12/28) (15), 82.7z in Sudan (19/23) (10). In contrast, in only two studies conducted in India, higher positivity rates, 93z (27/29) and 96z (24/25) were recorded by using skin biopsy specimens for PCR (12,13). However, the number of samples in these studies was too small to confirm the efficacy of PCR diagnosis.…”
mentioning
confidence: 53%
“…By this method parasites were readily detected in sections of tissues from 10 randomly selected seropositive dogs, whereas in Giemsa-stained sections it was possible to detect the parasites in only 70-80% of these animals. Using the same immunohistochemical staining, TAFURI et al 34 detected small numbers of amastigotes in the tissue of dogs with CVL in Minas Gerais State, south-eastern Brazil, and the same method has been used to detect other parasites such as Trypanosoma cruzi 6,26 , Toxoplasma gondii 7,22 and Leishmania (L.) donovani 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Dichos parámetros se calcularon aplicando las correcciones para la evaluación de pruebas diagnósticas con patrones de referencia imperfectos (16). Como patrón de referencia, en el estudio se usó la prueba ELISA rK39, cuya especificidad y sensibilidad han sido reportadas alrededor de 97% (17)(18)(19)(20)(21)(22)(23). Se determinaron los parámetros de sensibilidad, especificidad, valor diagnóstico positivo y negativo y razón de verosimilitud.…”
Section: Análisis Estadísticounclassified